Improving Cooperative’s Business Performance with Entrepreneurial Orientation and Organizational Culture Through Innovation - Kadek Diah Desita Giri; I Wayan Widnyana; Anak Agung Putu Agung (Journal of Business and Behavioural Entrepreneurship, 2022)
Cooperatives have the main goal of prospering its members which of course can be achieved by creating optimal business performance both in terms of financial and non-financial. This research was conducted with the aim of knowing the effect of entrepreneurial orientation and organizational culture on business performance directly and mediated by innovation. This research was conducted in Denpasar City with a population of 1,077 cooperative business units that are still active until 2020 and a sample of 292 cooperative heads. Data was collected by using interviews and questionnaires which were measured using a five-choice Likert Scale. Questionnaires were distributed using Google Forms and print outs. Data analysis was performed using Structural Equation Modeling-Partial Least Square (SEM PLS). The results of the analysis prove that entrepreneurial orientation has a positive and significant effect on business performance, organizational culture has a positive and significant effect on business performance, entrepreneurial orientation has a positive and significant effect on innovation, organizational culture has a positive and significant effect on innovation, and innovation has a positive and significant effect on business performance. The results of the mediation test prove that innovation mediates each of the effects of entrepreneurial orientation and organizational culture on business performance.